Antibiotic Bowel Decontamination in Gastrointestinal Surgery—A Single-Center 20 Years’ Experience - Schardey, Josefine; von Ahnen, Thomas; Schardey, Emily; Kappenberger, Alina; Zimmermann, Petra; Kühn, Florian; Andrassy, Joachim; Werner, Jens; Arbogast, Helmut; Wirth, Ulrich (Frontiers in Surgery, 2022)
Objective: Anastomotic leakage, surgical site infections and other infectious complications are still common complications in gastrointestinal surgery. The concept of perioperative antibiotic bowel decontamination demonstrated beneficial effects in single RCTs, but data from routine clinical use are still sparse. Our aim was to analyze the data from routine clinical use of perioperative antibiotic bowel decontamination in gastrointestinal surgery. Methods: Based on a 20 years’ experience we performed a retrospective analysis of all cases in oncologic gastrointestinal surgery with use of antibiotic bowel decontamination in gastric, sigmoid and rectal cancer. Clinical data and perioperative outcome were analyzed especially regarding anastomotic leakage, surgical site infections and other infectious complications. Results: A total of n = 477 cases of gastrointestinal surgery in gastric cancer (n=80), sigmoid cancer (n=168) and rectal cancer (n=229) using a perioperative regimen of antibiotic bowel decontamination could be included in this analysis. Overall, anastomotic leakage occurred in 4.4% (2.5 % gastric cancer; 3.0 % sigmoid cancer; 6.1 % rectal cancer) and surgical site infections in 9.6% (6.3 % gastric cancer; 9.5 % sigmoid cancer; 10.9% rectal cancer). The incidence of all infectious complications was 13.6% (12.5 % gastric cancer; 11.3 % sigmoid cancer; 15.7% rectal cancer). Mortality was low with an overall rate of 1.1% (1.3 % gastric cancer; 1.8 % sigmoid cancer; 0.4 % rectal cancer). Antibiotic decontamination was completed in 98.5 %. No adverse effects of antibiotic bowel decontamination could be observed. Conclusion: Overall, in this large cohort, we can report low rates of surgery-related serious morbidity and mortality when perioperative antibiotic bowel decontamination is performed. The rates are lower than other clinical reports. Therefore, the use of perioperative antibiotic bowel decontamination appears to improve patient safety and surgical outcomes during gastrointestinal oncologic procedures in a routine clinical setting.